Nanoformulation of Spirooxindole and Methods for Treating Hepatocellular Carcinoma - Assem Barakat; Fardous F. El-Senduny; Mohammad Shahidul Islam; Abdullah Mohammed Al-Majid; Yaseen A. M. M. Elshaier; Eman A. Mazyed; Farid A. Badria (Pharmaceutics)
Objectives: This in vivo study introduces a newly developed spirooxindole derivative that is deemed safe and effective as a potential targeted therapy for various cancers. Methods: Extensive in vivo investigations, including histopathology, immunohistochemistry, and molecular biology, validated its potential for further preclinical and clinical exploration, necessitating comprehensive examinations of its bioavailability, pharmacodynamics, and pharmacokinetics. Additionally, this study involves the development of a commercially viable proniosomal drug delivery system for the compound, facilitating controlled drug release. Results: The data revealed efficacy of spirooxindole derivative in halting the progression of liver cancer, metastasis, and portal vein thrombosis, with potential implications for enhancing regeneration and recovery of early-stage cancer cells in multiple organs, thereby improving recovery rates and remission among cancer patients. The proniosomes, loaded with the compound, exhibited high entrapment efficiency and prolonged drug release rates of up to 12 h in vitro. The optimized formula demonstrated superior drug release percentages and stability compared to conventional niosomes. Further analysis via FTIR and DSC confirmed the absence of chemical interactions and proper entrapment of the compound within the nanovesicles, indicating a stable and effective drug delivery system. Conclusions: This study presents a novel, safe, and effective chemical entity of spirooxindole derivatives for further preclinical and clinical studies.